Reflections on the value of autistic participation in a tri‐national teacher‐training project through discourses of acceptance, othering and power. (6th April 2018) - Wood, Rebecca; Milton, Damian
Abstract : The Transform Autism Education (TAE) project is a tri‐national teacher training scheme involving Greece, Italy and the UK, whose purpose is to set up training projects to facilitate the educational inclusion of autistic children. Running over three years from 2014 to 2017, the involvement of autistic participants has been the source of some discussion. Here, TAE team members Wood and Milton reflect on narratives of participation, acceptance and struggle which emerged during a workshop they ran in Greece. Derived from 11 non‐autistic and two autistic participants, and analysed via discourse analysis, these stories suggest a high value placed on autistic participation by non‐autistic TAE team members, but an unwitting tendency to 'other' autistic people and a lack of awareness of the power differential. Meanwhile, as the autistic team members describe how educational and social participation can be achieved, the implications for autism education researchers and practitioners are discussed.